(untitled) (REMUNOM, 2025)
Abstract: The processes of interactions and play in early childhood education provide children with relevant learning in the educational context. In this sense, this article explores the practices of early childhood education teachers, as well as the teaching methodologies and difficulties encountered in this process, aiming to analyze the practices carried out by these teachers in the classroom when it comes to free play and guided play. The methodology was carried out through field research, with an exploratory qualitative approach, based on interviews with four teachers of classes of 4 and 5 year-olds, from two schools in Linhares/ES, one in the public network and the other in the private network. It is understood, from the results, that free play and guided play are distinct processes, but inseparable and essential for the construction of effective practices in the development of the child. A diversity in the practices of the teachers carried out in the classroom was also observed. On the one hand, some teachers are constantly searching for new teaching methodologies and, on the other hand, some teachers still show a certain fragility, as they are attached to a fully programmed routine. Keywords: Free play. Directed play. Early childhood education.